The valuation book: How to value businesses and shares - An introductory guide for investors, managers and more - Aleksanyan, Mark; Lee, Kenneth; Meitner, Matthias; Pande, Neil (Hampshire (Great Britain) Harriman House Ltd., 2024)
Neil is a freelance financial training consultant, based in Canary Wharf in London. For over a decade, he has been a non-executive director of two private companies. He is also the investment manager for a family office, following value investing principles.